Spherical and Aspherical Lenses for Boosting the Performance of Terahertz Imaging Systems - El Hadj Abidi; Jaime Calvo‐Gallego; Alejandro Schulman; Miguel Ferrando‐Bataller; Oleg V. Minin; Igor V. Minin; Jesus E. Velázquez‐Pérez; Yahya Moubarak Meziani (Advanced Photonics Research)
A comprehensive study on the enhancement of terahertz (THz) detection through the terajet effect is performed using mesoscale dielectric lenses of different shapes and sizes. Polytetrafluoroethylene (PTFE) lenses, including spherical, aspherical, and cubic geometries, are fabricated and evaluated at frequencies of 0.15 and 0.3 THz. The lenses show enhanced responsivity and reduced noise‐equivalent power, with performance characteristics strongly dependent on frequency and shape. Aspherical lenses achieve superior spatial resolution at 0.3 THz, characterized by the smallest spot sizes and full width at half maximum. Although with a bigger spot size, spherical lenses show an increase of responsivity signal of a factor of 1.5 with respect to the aspherical lenses at 0.3 THz. Cubic lenses, on the other hand, exhibit significant signal strength enhancement at 0.15 THz, but not at 0.3 THz. A damping of Fabry–Pérot oscillations at higher frequencies is also observed, contributing to improved spatial resolution. These results demonstrate the potential of the terajet effect to optimize THz detection systems for diverse applications, including medical imaging, security screening, and nondestructive testing. The findings provide practical guidelines for designing advanced THz systems and emphasize the importance of tailoring lens configurations to specific operational requirements.